Augmented Reality Innovations for Showcasing East Kalimantan Sculptures: Evaluation and Development - Khosasih, Mikhael Ming; Lisana; Octavia, Erline (Universitas Pendidikan Ganesha, 2024)
Nowadays, there is a tendency among the younger generation to be less familiar with regional cultures in Indonesia, particularly the culture of statues, which are a heritage from our ancestors, such as the statues in East Kalimantan. Introducing these statues to the younger generation can help them understand the function of the statues and the appropriate behavior when encountering sacred statues. The objective of this research is to design an application equipped with augmented reality features and to evaluate the application to help the younger generation learn about and recognize the traditional statues of East Kalimantan. The analysis of the current situation was used to meet the needs in developing an application that displays 3D models along with information on the statues using augmented reality. This research employed a quantitative method involving 60 respondents. Each respondent completed a pre-test and a post-test, and the test results were compared using the paired sample t-test. The test results indicated a difference in the number of correct answers, with an average of 23 respondents on the pre-test and 58 respondents on the post-test. The results were statistically significant, with a value of 0.000. The evaluation was carried out through a questionnaire to determine the level of user satisfaction with the application. Based on the test and evaluation results, it was proven that the augmented reality application designed can enhance public knowledge about and recognition of the traditional statues of East Kalimantan.